Макромоделювання динамічних процесів в асинхронних машинах - Стахів, П.Г.; Васильчишин, І.І. (Технічна електродинаміка, 2011)
In proposed paper the methods of mathematical description for dynamic objects based on information about correlations between their external variables are proposed. They are developed using the test examples of electromechanical components with special features connected with mechanical and electromagnetic processes, nonlinear dependencies between variables characterizing their state and different time constants. As conducted research has shown the macromodels created based on optimization approach can ensure desired adequacy of modeling and make it possible to automate corresponding identification procedures.